Computed tomography imaging and clinical features of congenital hepatoblastoma: A retrospective analysis. Issue 31 (31st July 2020) - Li, Li; Liu, Wen; Wen, Rong; Jin, Ke
Abstract : Abstract: Congenital hepatoblastoma (CHB) is the most common hepatic malignant tumor of fetus or neonates, but few studies focusing on the radiological characteristics of CHB have been reported to date. To investigate the characteristic clinical and computed tomography (CT) findings of CHB to facilitate recognition and noninvasive diagnosis. Medical records of 7 patients with CHB were retrospectively reviewed. The demographic, clinical, and laboratory data were extracted from the electronic medical records. Two pediatric radiologists evaluated the abdominal CT examinations for the hepatic tumor location, size, enhancement characteristics, vascular invasion, and intra-/extra-hepatic metastasis. Among the included 7 patients (3 males and 4 females), only 1 had an elevated serum alpha-fetoprotein level. All patients had solitary intrahepatic mass with a mean size of 4.7 cm (range: 2.9–10.2 cm), of which liver SV-VII were most involved. 4/7 tumors were round while 3/7 irregular or lobulated. 6/7 tumors were well-defined. Microhemorrhage, cystic necrosis, and coarse calcification were present in 5/7, 4/7, and 1/7 tumors, respectively. All lesions showed inhomogeneously significant enhancement, with multiple nodular or striped appearance in the center and periphery of the tumors on the arterial phase, and then the enhancement area showed progressive expansion and fusion filling over time but the attenuation gradually declined on the portal and delayed phases, and finally the majority (6/7) of tumors presented multiple band- or island-like characteristics with prominently peripheral enhancement on the delayed phase while the remaining 1 relatively small tumor showed nearly complete but inhomogenous enhancement. In addition, only 1/7 tumor had hilar hepatic bile duct and portal vein invasion and secondary intra-hepatic bile duct dilation. No metastatic lesions were identified in all patients at diagnosis. The abdominal aorta distal to the coeliac trunk was significantly narrowed in 3/7 patients. Pathological examinations suggested that 6/7 tumors showed fetal histology with only 1 containing mesenchymal elements. The relationship between serum alpha-fetoprotein and CHB could be more complicated and yet to be determined. Dynamic contrast-enhanced CT can facilitate recognition and noninvasive diagnosis of CHB, presenting a pattern of progressive expansion and fusion filling but inhomogeneously significant enhancement.